LEGAL MEASURES ON THE PREVENTION OF RECIDIVISM OF RELEASED SEX OFFENDERS - Cholsaktrakul, Pornphet (Phranakhon Rajabhat Research Journal : Humanities and Social Sciences, 2019)
This research has a main objective of finding legal measures on the prevention of recidivism of released sex offenders that appropriate to the context of Thailand. In this research, the method of qualitative research was employed through the documentary research and in-depth interview, as well as the quantitative research was employed through the use of questionnaires. The findings of this research revealed that the suitable measures for Thailand were as follows: 1. An increase of capital punishment to be imposed on convicted rapists in cases where the injured persons suffer grievous bodily harm, where a child of age not exceeding 15 years old is raped, and where rape is committed under horrible circumstances; 2. Injections reducing sex hormones; 3. Rehabilitation of sex offenders by separating sex offenders from offenders of other crimes, or creating prison facilities particularly for sex offenders; 4. Sex offender registration; 5. Designation of safe zones for children; 6. Probation with specific conditions for sex offenders; and 7. Safety measures - the court shall be empowered to prescribe safety measures. This research suggests that 1. Section 39, section 276, section 277, section 277 bis shall be amended; 2. The Act on Injections to Reduce Sex Hormones B.E. … shall be drafted and enacted; and 3. The Act on Sex Offender Registration B.E. … shall be drafted and enacted.